Towards a systemic parameterisation of the environmental dimension (2011)
Information, particularly environmental information, constitutes a valuable asset which is fundamental in formulating, implementing and controlling environmental policy and management aimed at environmental sustainability. The systemic parameterisation of the so-called “environ-mental dimension” will lead to having enough, top-quality environmental information which has been duly collected, processed and prepared for developing any anthropic activity. The present article synthesises the results of a research project entitled, “A Systemic Parameterisation of the Environmental Dimension- Phase I,” carried out by the Policy, Information and Environmental Management (PIGA) research group; its main objective consisted of producing and proposing a theoretical basis and conceptual and methodological framework for developing such parameterisation.